Study of the Antioxidant Property Variation of Cornelian Cherry Fruits during Storage Using HPTLC and Spectrophotometric Assays - Anamaria Hosu; Claudia Cimpoiu; Luminita David; Bianca Moldovan (Journal of Analytical Methods in Chemistry)
Cornus species fruits are well known as a rich source of antioxidant compounds responsible for their diverse health benefits. The present study aims to investigate the variation of the total antioxidant capacity of Cornelian cherry (Cornus mas L.) fruits during storage, using high-performance thin-layer chromatography (HPTLC) and two spectrophotometric assays based on different mechanisms: the 2,2-azinobis(3-ethylbenzothiazolyne-6-sulphonic acid) radical cation (ABTS+∙) assay and the ferric reducing antioxidant power (FRAP) assay. The fruit extract was stored at room temperature (22°C) for 19 days. No major differences in the total antioxidant capacity were observed during this period, indicating that storage does not have any deleterious effect on the antioxidant properties of the investigated fruits extract. The antioxidant capacity varied between 12.91 and 12.83 µmol Trolox/g fruit as determined by the HPTLC method and from 36.13 to 33.93 µmol Trolox/g fruit as determined by the ABTS assay.